Septic Tank (ST)-Up Flow Anaerobic Filter (UFAF)-Subsurface Flow Constructed Wetland (SSF-CW) systems aimed at wastewater treatment in small localities in Colombia - Villegas Gómez, Juan David; Guerrero Erazo, Jhonniers; Castaño Rojas, Juan Mauricio; Paredes Cuervo, Diego (Rev. Téc. Fac. Ing. Univ. Zulia, 2010)
Véase archivo PDF